BILL NO. HB 19 AMENDMENT NO. (FOR DRAFTERS USE ONLY) SENATE ACTION HOUSE ACTION - MCWHEELER, P (Tufts Archival Research Center, 2007)
Incomplete; Amendment to bill H.B. 19 requiring employers to develop smoking policies designating smoking and non-smoking areas in the workplace. Includes details regarding the size and make-up of these sections.